Evaluation of insulin and C-peptide in diabetic patients undergoing renal dialysis - Annamala, P. T.; A. M., Anusha; Mathew, Teena (International Journal of Research in Medical Sciences, 2016)
Background: Patients with kidney failure associated with diabetes mellitus have disturbed responses of several glucoregulatory hormones. Diabetic nephropathy is the leading cause of end stage renal disease (ESRD). Renal failure is the progressive loss of function of kidney and patient requires a long renal replacement therapy, during which body’s waste products including urea, creatinine, glucoregulatory hormones and excess water are removed. Objectives of the study were to evaluate insulin and c-peptide concentrations in diabetic patients on renal dialysis and to compare the concentration of insulin, c-peptide, random blood glucose, urea and creatinine in pre and post dialysis samples of both controlled and uncontrolled diabetic patients. Methods: The study was conducted in 30 patients with diabetic kidney disease undergoing renal dialysis. The patients were grouped as controlled diabetics and uncontrolled diabetics based on their HbA1c levels. Pre and post dialysis blood samples were collected from patients. Concentration of insulin and c-peptide were analyzed by using ELISA methods. Random blood glucose (RBG), urea and creatinine were estimated by standard methods. Results: The patients were divided into 2 groups depending on their HbA1c levels as controlled and uncontrolled diabetes mellitus. The concentration of insulin, c-peptide, RBG, serum urea and creatinine showed statistically significant reduction in post dialysis samples when compared to pre dialysis in uncontrolled diabetics. But in case of controlled diabetes mellitus reduction was observed in the levels of insulin and c- peptide in post dialysis samples as compared to pre dialysis samples, but, the difference was not statistically significant. Conclusions: There are alterations in the levels of insulin, c-peptide and the glycemic status in diabetic patients during dialysis. This significant reduction may affect glucose metabolism in diabetic patients on dialysis. Hence, glycemic status should be continuously monitored in these patients.